Methodological Study for RAS Development for Chronic Pediatric Population - Manmeet Kaur; Gaurav Kohli; Manu Kohli (Indian Journal of Forensic Medicine & Toxicology, 2021)
Adolescence is considered as a difficult period filled with conflicts in search of self-autonomy, whichculminates the rediscovery of an individual towards adult life introduction. In addition to being sick thereare many other factors i.e. health care staff rotation, away from parents, experiencing pain during theprocedures, peer detachment and loss of self-esteem during hospitalization. The objective of the study wasto develop a scale for assessing resilience among children with Renal diseases. Methodological researchapproach was used for development of an effective Resilience Assessment Scale for children admitted withrenal diseases. Study was done on 75 children aged 10-18 years admitted with renal disease in MMIMS&RHospital, Mullana, Government Civil Hospital at Ambala and Kalpana Chawla Government Hospital atKarnal. The related review of literature ,experts guidance and investigator’s personal experience, a list offactors/domains were identified and compared with standardized Resilience scales i.e., Wagnild and YoungResilience assessment scale, Child and Youth Resiliency measure. Modified Delphi technique was used forContent validation of Resilience assessment scale with 9 experts Content validity was ascertained by expert’sopinion and was found to be 0.79.The range of rating score was 31-155 with the assumption that higherthe scores, the greater the resilience. At a cut-off point of ?102, the best balance between the sensitivityand specificity was achieved. Cronbach’s alpha and inter item correlation were used to measure internalconsistency of the tool, coefficient alpha was 0.81. Pearson correlation between resilience assessmentscale and Wagnild Young resilience scale was 0.84. In order to estimate stability test re-test reliability wascalculated and it came out to be 0.84.